The Relationship Between Body Mass Index, Work Period and Smoking With Low Back Pain Complaints Among Ironworkers in Babakan Village, Mataram City in 2025 - Aqilatunisa; I Wayan Tunjung; Henry Pebruanto; Deny Sutrisna Wiatma (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Low Back Pain (LBP) is a common musculoskeletal disorder among informal sector workers, including blacksmith workers, due to heavy physical workloads and non-ergonomic working postures. Individual factors such as Body Mass Index (BMI), length of employment, and smoking habits are suspected to increase the risk of LBP. Methods: This was an observational analytic study with a cross-sectional design. A total of 51 blacksmith workers were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected through anthropometric measurements, the Nordic Body Map questionnaire, and a smoking habits questionnaire. Data analysis was performed using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. Results: A significant association was found between BMI and low back pain complaints (p = 0.001; PR = 7,073; 95% CI: 1,090–45,883). Length of employment was also significantly associated with low back pain complaints (p = 0.004; PR = 3,850; 95% CI: 1.081–13.708). However, smoking habits were not significantly associated with low back pain complaints (p-value = 0.154; 95% CI: 1.039–2.338; PR: 1.558). Conclusion: Body Mass Index and length of employment are significantly associated with low back pain complaints among blacksmith workers, while smoking habits show no significant association. Preventive efforts should focus on weight control and regulation of work duration and workload.